(untitled) (Modern education and development, 2025)
The portal vein plays a critical role in liver physiology by transporting nutrient-rich blood from the gastrointestinal tract and spleen to the liver. This review highlights the anatomy, development, and major functions of the portal vein, emphasizing its importance in metabolic processes and homeostasis. Understanding the portal vein is essential for diagnosing and treating hepatic and systemic diseases.